Characteristics of and treatment outcomes in rifampicin-intolerant patients - R. Mangat; S.K. Brode; H.K. Mah; M.S. Brar; N.F. Sabur (IJTLD Open)
BACKGROUND: Rifampicin (RIF) is considered the backbone of TB treatment, but adverse effects often limit its use. METHODS: This retrospective cohort study examined patients treated for TB disease at our institution, and compared those who received RIF to those who were intolerant to RIF. RESULTS: A total of 829 patients were included. Seventy-six patients (9%) were intolerant to RIF. Patients with RIF intolerance were significantly older (median age: 67 years, IQR 50–78 vs. 48 years, IQR 31–70; P < 0.0001), and were more likely to be female (57% vs. 41%; P = 0.01) and have concurrent diabetes mellitus (37.3% vs. 19%; P < 0.0001) compared to those who tolerated RIF. RIF intolerance was most commonly due to transaminitis (25%), cytopenia (14.5%), rash (17.1%) and gastro-intestinal intolerance (7.8%). Twenty patients were subsequently challenged with rifabutin, and this was successful in 70%. The mean treatment duration was significantly longer in patients who were intolerant to RIF (335 vs. 270 days; P < 0.001). There was no significant difference in treatment outcomes. CONCLUSION: RIF intolerance is more common in older patients, females, and those with concurrent diabetes mellitus. Patients who could not tolerate RIF had a longer duration of therapy, but no difference in treatment outcomes. When attempted, rifabutin was well tolerated in most patients with a previous RIF-related adverse event.